Evidence for morphological restructuring in the second person pronoun in early English correspondence - Rutkowska, Hanna (Wydawnictwo Naukowe UAM, 2007)
The focus of this article is morphosyntactic. Its aim is to provide evidence for a particular type of syntactic reanalysis which is likely to have contributed to the establishment of you as a universal form of the second person pronoun in both subject and oblique positions. The paper discusses structures containing verbs such as PRAY and BESEECH. My analysis shows that the confusion between the imperative and subjunctive moods, frequent in these constructions, is a plausible explanation for the weakening of the case distinction and the spread of the you form to the subject position in the sentence.
Keywords: zaimek osobowy; personal pronoun; morfoskładnia; morphosyntax; język późny średnioangielski; Late Middle English; Anglia; England; korespondencja piętnastowieczna; fifteenth-century correspondence